PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS PADLET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SMP NEGERI 1 BONTONOMPO KABUPATEN GOWA - Dian Safitri; Irmawati Thahir; Firdaus Rahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Padlet is an application that allows teachers and students to share text, images, videos, links, or documents in one collaborative page. The purpose of this study was to determine the effect of using Padlet-based e-learning media on student learning outcomes in Islamic Religious Education subjects for class VII at SMP Negeri 1 Bontonompo, Gowa Regency. This study used a quantitative approach with an experimental method. The population in this study was 353 students, and the sampling technique was carried out using simple random sampling of 78 students. The results of the descriptive analysis showed that student activity in learning increased, from 80% at the first meeting to 93% at the second meeting, which was included in the good category. In addition, student learning outcomes before using Padlet showed a low level of completeness. However, after the application of Padlet-based e-learning media, 92% of students achieved the Minimum Completeness Criteria (KKM), with 63 students experiencing a significant increase in learning outcomes. Based on the hypothesis test using the t-test at a significance level of 0.10, the calculated t value (6.02)> t_table (1.294) was obtained, so H₀ was rejected and H₁ was accepted. This means that there is a significant influence between the use of Padlet-based e-learning media on student learning outcomes. The results of this study support media theory, influence theory, and learning outcome theory, and show that the use of Padlet media is effective in improving Islamic Religious Education learning outcomes.